Red Tape Phenomenon of Social Securities Distribution During Covid-19: A Socio–Legal Analysis - Mailinda Eka Yuniza; Aicha Grade Rebecca (Center for Southeast Asian Social Studies (CESASS), 2021)
To distribute social aids during a time of a pandemic, red tapes or unnecessary bureaucratic layers needs to be eliminated because the situations demand flexibility. In fact, during the Covid-19 the Indonesian government struggled to hand the staple needs help due to various problems with the existing social aid system. The purpose of this study is to analyze the social and legal factors that create a red tape that hindered the implementations of distributions. This research uses a qualitative approach with data collection techniques of literature and statutory analysis. The result of this study shows that there is an interplay factor between administrative law on social policies and the bureau pathology(Bureaucratic disease) that infects the bureaucratic system of the Ministry of Social Affairs especially in the aspects of managerial, human resources, and tendencies to conduct unlawful actions aspects. The format of the law has proven to be ineffective to be used in a pandemic setting. Furthermore, there are tendencies of upholding the tight legal mechanism to share the responsibilities in between bottom-up government units which had created ineffective within the systems in times of a pandemic. Nevertheless, it shows that the law has already matured in governing the bureaucratic nature in the Ministry of Social Affairs.